Analisis Faktor-Faktor yang Berpengaruh Terhadap Konservatisme Akuntansi - Eko Hariyanto (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
This study aims to analyze whether the factors that affect accounting conservatism. Data is taken from secondary data on real estate and property companies that have sold their shares on the Indonesian Stock Exchange from 2016 to 2019, the number of selected samples is 23 companies. The variables used are profitability, firm size, institutional ownership and managerial ownership. All variables are measured by ratio data. Data analysis using multiple regression which is processed by the SPSS program.The results showed that profitability and managerial ownership had a positive effect on accounting conservatism. Firm size has a negative effect on accounting conservatism, while institutional ownership has no effect on accounting conservatism.